MEMBANGUN CITRA MEREK DI HARI SARAPAN NASIONAL: Program Aktivasi Merek “Free Egg McMuffin” McDonald Indonesia - Raditya, Fakhri; Agustini, Prima Mulyasari (Journal Communication Spectrum : Capturing New Perspectives in Communication, 2015)
Brand activation programs have become the mainstay weapons of marketing communications for marketers or brand managers today. Many creative programs were launched to bring consumers and brands closer, to create a pleasant and meaningful consumer experience, and to build a positive image in consumers' minds about brands. This article examines the extent of the effect of the brand activation program on the brand image by utilizing special moments at a fast-food restaurant outlet, McDonald's. This global branded restaurant launches the "Free Egg McMuffin" program to customers in welcoming the National Breakfast Day. Using a quantitative approach, a set of questionnaires was distributed to 100 respondents. Cluster sampling was chosen because of the heterogeneous nature of the respondents. The results of the regression analysis showed that the brand activation variable significantly and positively affected 42.2% of the brand image variable, while the dimensions that had the most positive impact on brand activation were interesting and beneficial factors. This study supports the power of brand activation programs in encouraging the creation of positive images related to brands. Thus, marketers can enhance the attractiveness and benefits of the program through content creativity and context in order to have the maximum impact on brand image amplification.